Role of phospholamban phosphorylation on Thr17 in cardiac physiological and pathological conditions - Mattiazzi, Alicia Ramona (2005)
The sarcoplasmic reticulum (SR) Ca2+-ATPase (SERCA2a) is under the control of a closely associated SR protein named phospholamban (PLN). Dephosphorylated PLN inhibits the SR Ca2+ pump, whereas phosphorylation of PLN, at either Ser16 by PKA or Thr17 by calmodulin-dependent protein kinase II (CaMKII), reverses this inhibition, thus increasing SERCA2a activity and the rate of Ca2+ uptake by the SR. This would in turn lead to an increase in the velocity of relaxation, SR Ca 2+ load, and myocardial contractility. Thus, PLN is a major determinant of cardiac contractility and relaxation. Although in the intact heart, β-adrenoceptor stimulation results in phosphorylation of PLN at both Ser16 and Thr17 residues, the role of Thr17 site has long remained equivocal. In this review, we attempt to highlight the signaling cascade and the physiological relevance of the phosphorylation of this residue in the heart under both physiological and pathological situations.